Asuhan Keperawatan pada Klien dengan Nyeri Akut Menggunakan Intervensi Relaksasi Nafas dalam di Ruang Mawar Pink RSUD Sidoarjo - Khotimah, Husnul; Jahro, Siti Fatimatus; J.A.H, Maulidiyah (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Hypertension is a chronic condition that cannot be cured but can be managed by modifying risk factors. Acute pain, such as headaches, is a common symptom among hypertensive patients and can be alleviated through non-pharmacological approaches like deep breathing relaxation techniques. This study aimed to evaluate the effectiveness of deep breathing relaxation therapy for reducing acute pain in hypertensive patients. Using a case study method, data were collected through interviews, observations, physical examinations, and documentation in the Mawar Pink Room at Sidoarjo Hospital. The intervention involved three sessions of 10-minute deep breathing relaxation therapy over three days. Results indicated significant pain reduction, as measured by numerical pain scales, demonstrating the therapy's efficacy in alleviating acute pain and lowering blood pressure. The findings suggest that integrating deep breathing relaxation techniques into nursing care plans offers a valuable, non-invasive strategy to manage pain and improve patient outcomes in hypertensive care.